Utilisation of Rosehip Waste Powder as a Functional Ingredient to Enrich Waffle Cones with Fibres, Polyphenols, and Carotenoids - Alexandra Raluca Borşa (Bogdan); Adriana Păucean; Melinda Fogarasi; Floricuța Ranga; Andrei Borșa; Anda Elena Tanislav; Vlad Mureșan; Cristina Anamaria Semeniuc (Foods)
The solid waste generated from processing rosehip fruits into jam is valuable due to its rich content in fibres, polyphenols, and carotenoids; it could be valorised as a functional ingredient in a powder form to enrich food products. This study aimed to test its potential as a value-added ingredient, especially to enrich waffle cones with fibres, polyphenols, and carotenoids. In this regard, four formulations of waffle cones were prepared by partially substituting wheat flour with rosehip waste powder at 0%, 10%, 15%, and 20%, reaching concentrations of 0%, 3.7%, 5.7%, and 7.5% of the total batter, respectively. These were assessed for their sensory, textural, and techno-functional properties; proximate composition (including crude fibre); energy value; pH; and colour, as well as the content of carotenoids and polyphenols. The contribution of rosehip powder to the production cost of these waffle cone formulations was also determined. The results showed that using rosehip waste powder as an ingredient reduced the waffle cones powder’s capacity to hold water (from 3.11 g/g to 2.64–3.08 g/g) and to swell (from 4.98 mL/g to 4.23–4.48 mL/g), while it increased their oil-holding capacity (from 0.93 g/g to 0.96–1.19 g/g) and the content in fibre (from 1.58% to 3.41–4.83%), polyphenols (from 400.70 µg/g to 1732.26–2715.69 µg/g), and carotenoids (from n.d. to 6.86–14.28 µg/g); however, the solubility (72.65–75.33%), hardness (2.31–2.83 N), and fracturability (6–8) were not significantly influenced. The sensory acceptability of enriched waffle cones (92–93%) was higher than that of control waffle cones (90%). The production cost of a waffle cone increased by EUR 0.004–0.009 when wheat flour was substituted by rosehip powder in concentrations of 10–20%. In conclusion, to enrich waffle cones with fibres, polyphenols, and carotenoids, at least 10% of wheat flour must be substituted with rosehip waste powder in their manufacturing recipe.